2011
DOI: 10.2109/jcersj2.119.234
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ni and Cr on the stability of leakage current for spinel-reduced ZnO varistor ceramics

Abstract: With a new concept of reducing the spinel particles in ZnO varistor ceramics (ZVC), the molar ratio of Sb 2 O 3 (M S )/Bi 2 O 3 (M B ) and the effect of the sintering temperature (T S ) on densification behavior and varistor voltage (V b : V 1mA /mm) were investigated. The densification behavior of ZVC during the sintering process was significantly affected by the M S /M B , and the densification curve was shifted to a lower temperature with a decreasing M S /M B . Based on these experimental results, four typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…It has been reported that cations such as Co, Ni or Mn were incorporated in order to improve the properties of the varistor and its stability. 18,19 Peiteado obtained optimized varistors by adding both TiO 2 and SiO 2 , the titanium cations thus can enter in the spinel lattice and stabilize this phase, and SiO 2 reacts with ZnO to form the insulating Zn 2 SiO 4 phase.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that cations such as Co, Ni or Mn were incorporated in order to improve the properties of the varistor and its stability. 18,19 Peiteado obtained optimized varistors by adding both TiO 2 and SiO 2 , the titanium cations thus can enter in the spinel lattice and stabilize this phase, and SiO 2 reacts with ZnO to form the insulating Zn 2 SiO 4 phase.…”
Section: Introductionmentioning
confidence: 99%
“…The exceptional capacity of the spinel grains to dissolve and incorporate other oxide additives makes this option more feasible: the spinel lattice is a fairly open structure that easily accommodates additional cations on its tetrahedral and octahedral empty sites . The fact is that for long, it has been monitored that oxides like Co, Mn, Ni, and particularly Cr, which are incorporated to enhance the varistor electrical nonlinearity and/or stability to degradation, also diffuse into the spinel grains and to some extent stabilize this phase against its expected decomposition to pyrochlore . But even so a certain amount of Py is yet obtained in the sintered samples, and the leakage current values are still elevated.…”
Section: Introductionmentioning
confidence: 99%